Pengaruh Tunjangan Kinerja dan Komunikasi Internal terhadap Motivasi Kerja Pegawai Dinas X - Dinda Safitri Dewi; Andi Heru Susanto (CV. Ulil Albab Corp, 2022)
Performance allowances and good and appropriate internal communication will be employee motivation. With high employee work motivation, it can improve the performance and goals of the employee agency to the maximum. Therefore, this study aims to determine the effect of performance allowances and internal communication on employee motivation. This research is a quantitative research in which the data analysis techniques used are multiple linear regression test, simultaneous test (f), partial test (t) and coefficient of determination test (R2). The number of samples in this study were 100 respondents with 25 statements on the questionnaire. The results of the study indicate that there is a positive and significant effect between performance allowances and internal communication either simultaneously or partially on the work motivation of the employees of the Pontianak City Bappeda Office; The results of the R2 test show that the performance allowance and internal communication variables are 76%, while the remaining 24% is explained by other variables that are not used in this study. Limitations in this study include using two independent variables and only carried out in service X with the use of a limited sample, so the results obtained cannot be generalized..